Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3996/042011-jfwm-027
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Acoustical Activity of Bats Prior to and Following White-Nose Syndrome Occurrence

Abstract: White-nose Syndrome (WNS), a wildlife health concern that has decimated cave-hibernating bat populations in eastern North America since 2006, began affecting source-caves for summer bat populations at Fort Drum, a U.S. Army installation in New York in the winter of 2007–2008. As regional die-offs of bats became evident, and Fort Drum's known populations began showing declines, we examined whether WNS-induced change in abundance patterns and seasonal timing of bat activity could be quantified using acoustical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
93
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 40 publications
(52 reference statements)
9
93
4
Order By: Relevance
“…While some small successional change in forested environments did occur over the course of our 8‐year study, the habitat conditions within the riparian areas where we focused our study were relatively unchanged. Development was spatially concentrated in the south‐eastern corner of the installation, with the remainder of the installation consisting of 18 training areas, an airfield and a large, centralized ordnance impact zone that are all largely undeveloped (Dobony et al ., ; Ford et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…While some small successional change in forested environments did occur over the course of our 8‐year study, the habitat conditions within the riparian areas where we focused our study were relatively unchanged. Development was spatially concentrated in the south‐eastern corner of the installation, with the remainder of the installation consisting of 18 training areas, an airfield and a large, centralized ordnance impact zone that are all largely undeveloped (Dobony et al ., ; Ford et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Nine bat species have been documented on Fort Drum, including: MYLU, MYSO, MYSE , MYLE, silver‐haired bat ( Lasionycterius noctivagans , LANO), PESU, EPFU, eastern red bat ( Lasiurus borealis , LABO) and hoary bat ( Lasiurus cinereus , LACI). During the winter of 2007–2008, WNS appeared in area hibernacula, resulting in mass overwinter mortality and dramatic declines in summer activity by at least 3 of the most commonly encountered bat species (MYLU, MYSE and MYSO) since 2008 (Ford et al ., ). In particular, MYLU suffered a precipitous population decline post‐WNS (Dobony et al ., ; Ford et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…By early 2009, WNS had been documented at most hibernacula throughout the Northeast, causing precipitous declines in wintering populations of Myotis lucifugus (LeConte) (Little Brown Myotis) (Frick et al 2010a, Langwig et al 2012). Acoustic monitoring indicated that activity of Little Brown Myotis on the summer landscape also decreased over 70% after arrival of WNS (Brooks 2011, Dzal et al 2011, Ford et al 2011). Accordingly, most summer colonies in the area also declined dramatically in size (e.g., Frick et al 2010b, Fuller et al 2012).…”
mentioning
confidence: 99%
“…Also rare and endangered species, like Myotis sodalis, suffer from the disease [15], and strong decrease in activity of Myotis spp. during summer was recorded in the areas surrounding underground roosts affected by WNS [16].…”
Section: Introductionmentioning
confidence: 99%